2001
DOI: 10.1002/ffj.978
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils of Hypericum olympicum L. and Hypericum perforatum L.

Abstract: The essential oil of Hypericum olympicum L. was analysed for the first time and was compared to the essential oil of Hypericum perforatum L. from the same location. Eighteen components were common for both species. The main components of H. olympicim oil were (E)-anethole (30.7%) andˇ-farnesene (12.4%), and for H. perforatum oil they wereˇ-caryophyllene (14.2%) and 2-methyl-octane (13.1%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The ability to control self-assembly is of overwhelming importance in the fabrication of synthetic colloids tailored for targeted applications, 14,15 such as the delivery of drugs in the human body [16][17][18] or the addition of bioactive substances to foods. 19,20 Recently, we have investigated by Monte Carlo simulation the low-temperature structure of a dilute mixture of dimers (made up of two spherical monomers of unequal size) and spheres. [21][22][23] In these studies, an additional attraction takes place between spheres and the small monomers.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to control self-assembly is of overwhelming importance in the fabrication of synthetic colloids tailored for targeted applications, 14,15 such as the delivery of drugs in the human body [16][17][18] or the addition of bioactive substances to foods. 19,20 Recently, we have investigated by Monte Carlo simulation the low-temperature structure of a dilute mixture of dimers (made up of two spherical monomers of unequal size) and spheres. [21][22][23] In these studies, an additional attraction takes place between spheres and the small monomers.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the fragrance microcapsules and PANI fragrance microcapsules weight loss involve two stages. The first stage is in the range of 25–233°C mainly because of the loss of the fragrance, and the second stage ranging from 376°C to 479°C is caused by the decomposition of wall material 21,22 . As can be seen from the DTG curves, compared with essential oil, the maximum weight loss rate temperature for the fragrance capsules is increased from 127°C to 169°C, indicating that the wall material plays an important role in protecting essential oil from losing at high temperature conditions.…”
Section: Resultsmentioning
confidence: 94%
“…There are a few reports in literature on the volatile compounds of HOE. Gudžić et al (2001) identified 49 compounds and Pavlović et al (2006) found 41 compounds including alkanes, monoterpenes, sesquiterpenes and oxygenated compounds. Moreover, Stojanovic et al (2003) has determined 14 alkanes and 11 fatty acids in H. olympicum.…”
Section: Discussionmentioning
confidence: 99%